2004
DOI: 10.1631/jzus.2004.1570
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic effects of chromium trioxide on root tip cells of Vicia faba

Abstract: In this study on the mutagenic effects of different concentrations of chromium trioxide (CrO(3)) on Vicia faba root tip, micronucleus assay and chromosome aberration assay were used to determine the mitotic indexes, micronucleus aberration rate and chromosome aberration rate of Vicia faba root tip cells. The results showed that the effects of CrO(3) concentration on the mitotic indexes were complicated. CrO(3) increases the micronucleus aberration rate of Vicia faba root tip cells. It was found that within cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 3 publications
3
24
0
1
Order By: Relevance
“…The variation of chromosomal aberrations with the different test liquids was however not dose-dependent. This is in agreement with Odeigah et al (1997) but in contrast to the observations by Qian (2004) who reported that chromosome aberration increased with increasing effluent concentration. A possible explanation for the former is that with increasing concentration, and consequently increasing toxicity, there was an inhibitory effect on cell division.…”
Section: Microscopic Effectssupporting
confidence: 91%
“…The variation of chromosomal aberrations with the different test liquids was however not dose-dependent. This is in agreement with Odeigah et al (1997) but in contrast to the observations by Qian (2004) who reported that chromosome aberration increased with increasing effluent concentration. A possible explanation for the former is that with increasing concentration, and consequently increasing toxicity, there was an inhibitory effect on cell division.…”
Section: Microscopic Effectssupporting
confidence: 91%
“…Laggard chromosomes depend upon the moving speed and process of an individual chromosome differing from normal ones (Qian 2004). Rivetta et al (1997), found that Cd binds to CAM calmodulin and competes with Cd in these bindings.…”
Section: Resultsmentioning
confidence: 99%
“…Then they were stored in 70% ethanol at a temperature of +4 C. After they were hydrolyzed in 1 N HCl at a temperature of 60 C for 20 min, they were treated with 45% acetic acid solution for 30 min, and stained with acetocarmine for 24 h. In the last stage, the root tips were crushed in 45% acetic acid and photographed at 500 zoom with a binocular research microscope (Qian 2004, Staykova et al 2005.…”
Section: Micronucleus Assay and Chromosomal Aberrationsmentioning
confidence: 99%